Dependence of the Russian Economy on Oil Prices in the Context of Volatility of the Global oil Market: Articulation of Issue - Pavlova, Elena Vladimirovna; Duborkina, Irina Albertovna; Sokolova, Antonina Pavlovna; Doronkina, Irina Gennadiyevna; Konovalova, Elena Evgeniyevna (International Journal of Energy Economics and Policy, 2017)
At the present stage, oil is not just commodity but also a kind of asset, the value of which is associated with multiple financial processes. The impact of oil prices is particularly strong in the countries where trade in energy commodities has reached a high level in total exports. Russia belongs to such countries as well. Oil industry is one of the most important areas for supporting the economy development in Russia. Therefore, there is a need to develop measures for proper functioning of the oil industry, as it provides a significant share of Russia’s GDP and budget revenues. Besides, about 80% of foreign investment goes directly to the oil and gas sector. In addition, the long-term dependence of the Russian economy on energy resources has led to decline in incentives for the development of other industries and creation of new technologies. The article explores the issues of dependence of the Russian economy on global oil prices and factors that influence the situation on the global oil market; the increasing role of the financial market of oil contracts in the context of the current economic development is substantiated. This article examines the situation when the country’s export is largely focused on energy, while other industries significantly lag behind; it is described in the economic theory as a phenomenon dubbed "Dutch disease". This phenomenon is described by increase in extraction and export of commodities; besides, the influx of capital from exports stimulates consumer demand, but the industrial sector fails to keep up with the growth of the household income due to the pressure of the "Dutch disease", which ultimately increases inflation. In addition, this results in lagging of the processing sector of the economy behind the extractive sector. Keywords: oil market, World Trade Organization, reserve fund, economy JEL Classifications: O10, F10